Developing a spatial planning information package in ISO 19152 land administration domain model. (November 2020) - Indrajit, Agung; van Loenen, Bastiaan; Ploeger, Hendrik; van Oosterom, Peter
Highlights: The Land Administration Domain Model (LADM), ISO 19152:2012, offers guidelines to construct interoperability between land tenure, land valuation, land use and land development. This article discusses: Standardization of spatial planning information as a subset of land management information. Accommodating Rights, Restrictions, and Responsibilities from spatial planning process. Development of spatial planning information package in the existing LADM standard. Abstract: Cities establish and maintain Land Administration Systems (LAS) to manage information about the land and urban space. Recognizing the importance of the urban space for sustainable development, information from spatial planning will affect land administration and vice versa. Therefore, every aspect that influences land use, both from spatial planning and land administration should be identified, documented, and standardized as they contain legally binding rules for governments and citizens. The Land Administration Domain Model (LADM), ISO standard 19152:2012, offers guidelines to ensure interoperability in the representation of Rights, Restrictions, and Responsibilities (RRRs). LADM is also capable of standardizing multi-dimensional representation, including the temporal capability for documenting and visualizing all legal aspects of land use or space. This paper discusses how to construct interoperable information between the spatial plan and land administration. We present the standardization of spatial planning information and land administration as subsets of land-related information. The paper proposes the development of a spatial planning package within the existing LADM standard.